2018
DOI: 10.1523/jneurosci.0363-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Medial Olivocochlear System Prevents Hidden Hearing Loss

Abstract: Cochlear synaptopathy produced by exposure to noise levels that cause only transient auditory threshold elevations is a condition that affects many people and is believed to contribute to poor speech discrimination in noisy environments. These functional deficits in hearing, without changes in sensitivity, have been called hidden hearing loss (HHL). It has been proposed that activity of the medial olivocochlear (MOC) system can ameliorate acoustic trauma effects. Here we explore the role of the MOC system in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 60 publications
10
75
0
Order By: Relevance
“…1A). As recently shown (Boero et al, 2018), no abnormalities in peak I amplitude were observed in L9’T compared to WT mice at 8, 16 and 32 KHz either at P16 (Table 1) or P21 (Fig. 1B; Table 1).…”
Section: Resultssupporting
confidence: 83%
“…1A). As recently shown (Boero et al, 2018), no abnormalities in peak I amplitude were observed in L9’T compared to WT mice at 8, 16 and 32 KHz either at P16 (Table 1) or P21 (Fig. 1B; Table 1).…”
Section: Resultssupporting
confidence: 83%
“…These might indicate differential effects in the maturation of different nuclei of the auditory pathway in mutant mice. As recently shown (Boero et al, 2018), no abnormalities in peak I amplitude were observed in L9ЈT compared with WT mice at 8, 16, and 32 kHz, either at P16 or P21 ( Fig. 2B; Table 1).…”
Section: Reduction Of Abr Wave III Amplitude In L9t Micesupporting
confidence: 79%
“…The functions of medial olivocochlear (MOC) neurons are thought to inhibit cochlear activity via synapses onto cochlear outer hair cells (OHCs), and subsequently alter OHC electromotility and basilar membrane mechanics (Fex, 1967;Mountain, 1980;Siegel and Kim, 1982;Guinan, 1996Guinan, , 2010Elgoyhen and Katz, 2012). MOC neurons thereby exert a variety of downstream effects, including adjusting cochlear gain to respond to sound intensity spanning orders of magnitude (Galambos, 1956;Desmedt, 1962;Wiederhold and Peake, 1966;Wiederhold and Kiang, 1970;Geisler, 1974;Guinan and Gifford, 1988), improved hearing in background noise (Winslow and Sachs, 1987;Kawase et al, 1993), protection against noise-induced trauma (Rajan, 1988(Rajan, , 1995Reiter and Liberman, 1995;Taranda et al, 2009;Maison et al, 2013;Tong et al, 2013;Boero et al, 2018), and auditory attention (Oatman, 1976;Glenn and Oatman, 1977;Delano et al, 2007;Terreros et al, 2016). Disorders such as tinnitus and hyperacusis may alter the function of MOC neurons (Attias et al, 1996;Knudson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%